2003
DOI: 10.1086/346053
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood Bactericidal Activity during Treatment of Pulmonary Tuberculosis

Abstract: The timely evaluation of new drugs that can be used to shorten tuberculosis (TB) treatment will require surrogate markers for relapse. This study examined bactericidal activity against intracellular Mycobacterium tuberculosis in whole blood culture (whole blood bactericidal activity; WBA) during TB treatment. In the absence of chemotherapy, immune mechanisms in patient blood resulted in bacteriostasis, whereas administration of oral chemotherapy resulted in bacillary killing. Total WBA per dose was greater dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 45 publications
1
60
2
Order By: Relevance
“…The isolates in the present study were passaged in vitro only twice prior to their introduction into cell culture to avoid the attenuation we had previously observed with isolate MP-28. When studied in 2000, that isolate showed nearly 1-log intracellular growth in whole blood culture (1,16); by the following year, it had become markedly attenuated (19). Similar attenuation may have occurred with CDC1551, an outbreak-associated isolate that was highly virulent when first studied in mice in 1998 (13).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The isolates in the present study were passaged in vitro only twice prior to their introduction into cell culture to avoid the attenuation we had previously observed with isolate MP-28. When studied in 2000, that isolate showed nearly 1-log intracellular growth in whole blood culture (1,16); by the following year, it had become markedly attenuated (19). Similar attenuation may have occurred with CDC1551, an outbreak-associated isolate that was highly virulent when first studied in mice in 1998 (13).…”
Section: Discussionmentioning
confidence: 80%
“…Isolates were collected prospectively in a study of surrogate markers of the response to chemotherapy conducted in Vitória, Brazil (19). Briefly, subjects were 18-to 60-year-old human immunodeficiency virus type 1-seronegative patients with newly diagnosed initial episodes of sputum smear-positive pulmonary tuberculosis.…”
Section: Mycobacterial Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in agreement with those reported by Rastogi et al (13) but are in sharp contrast to the data reported by Orme and colleagues (16), in which a reduction of 3 log 10 CFU/ml over a narrow concentration range between 0 and 1 mg of isoniazid per liter was observed with intracellular M. tuberculosis Erdman in murine macrophages. The whole-blood system has advantages over a macrophage monolayer system; for example, plasma protein binding and immune components can be factored in, thereby mimicking the in vivo situation closely (18). Furthermore, exposures up to 2,560-fold higher than the concentration producing stasis can be studied in comparison to the exposures possible in the macrophage monolayer system (640-fold higher).…”
Section: Discussionmentioning
confidence: 99%
“…An ideal marker would measure events early during treatment and be accurate regardless of the mechanism of drug action or the regimen being tested. In addition to serial sputum culture conversion, less well studied biomarkers of response to therapy include sputum 85B protein and mRNA (2,17), sputum cytokines (15), and whole-blood bactericidal activity (18). None has been adequately validated to demonstrate long-term efficacy in phase 3 trials.…”
mentioning
confidence: 99%